2016
DOI: 10.1016/j.celrep.2016.04.080
|View full text |Cite
|
Sign up to set email alerts
|

Striking Immune Phenotypes in Gene-Targeted Mice Are Driven by a Copy-Number Variant Originating from a Commercially Available C57BL/6 Strain

Abstract: We describe a homozygous copy number variant that disrupts the function of Dock2 in a commercially available C57BL/6 mouse strain that is widely used for backcrossing. This Dock2 allele was presumed to have spontaneously arisen in a colony of Irf5 knockout mice. We discovered that this allele has been inadvertently backcrossed into multiple mutant mouse lines, including two lines engineered to be deficient in Siae and Cmah. This particular subline of C57BL/6 mice also exhibits several striking immune phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 31 publications
(45 reference statements)
4
50
1
1
Order By: Relevance
“…Six to eight weeks old male C57BL/6 wild-type and Cmah −/− mice with a human-like deletion in the exon 6 of the Cmah gene (Hedlund et al, 2007) were used. The Cmah −/− mice were negatively tested for a dock2 mutation, recently shown to be present in some of these mice due to backcrossing into commercially available C57BL/6 mice (Mahajan et al, 2016). Sedation was performed by inhalation of 4% isoflurane or by intraperitoneal injection of 80 mg kg −1 Ketamin and 5 mg kg −1 Rompun (Bayer AG) according to their body weight.…”
Section: Methodsmentioning
confidence: 99%
“…Six to eight weeks old male C57BL/6 wild-type and Cmah −/− mice with a human-like deletion in the exon 6 of the Cmah gene (Hedlund et al, 2007) were used. The Cmah −/− mice were negatively tested for a dock2 mutation, recently shown to be present in some of these mice due to backcrossing into commercially available C57BL/6 mice (Mahajan et al, 2016). Sedation was performed by inhalation of 4% isoflurane or by intraperitoneal injection of 80 mg kg −1 Ketamin and 5 mg kg −1 Rompun (Bayer AG) according to their body weight.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the genetic variability among mouse strains has been focused on SNPs; however, variation in structure of DNA regions affecting DNA sequence length and/or orientation that includes deletions, insertions, copy-number gains, inversions, and transposable elements, may also underpin susceptibility traits [26]. In addition, while inbred mouse strains are considered isogenic, intra-strain differences and their influence on experimental outcomes have been identified [27, 28]. …”
Section: Genetic Variabilitymentioning
confidence: 99%
“…As illustrated in Table 2, some immune relevant genetic variations among C57BL/6 substrains include a Nlrp12 mutation in C57BL/6J mice and a Dock2 mutation in C57BL/6NHsd mice from certain colonies. 55,77 The Nlrp12 gene primarily controls neutrophil chemotaxis in response to bacterial invasion. C57BL/6J mice carry a missense, loss of function mutation (Nlrp12 C57BL/6J ) and are more susceptible to certain bacterial infections compared with other C57BL/6 substrains harboring the wild-type Nlrp12 allele.…”
Section: Immune Relevant Variations Among Substrainsmentioning
confidence: 99%
“…The Dock2 Hsd mutation was revealed when reduced splenic marginal zone B cells and increased numbers of CD8+ T cells were identified in C57BL/6NHsd (and derived mutant mice) relative to other C57BL/6N mice. [77][78][79] Subsequently, Envigo tested their mice and reported that this mutation (Dock2 Hsd ) was present in 6 of their 19 C57BL/6NHsd colonies (http://www.envigo.com/ assets/docs/c57-customer-communication-2-final-9jun16.pdf). Many research programs maintain in-house colonies of genetically engineered animals and "wild-type" background strains that warrant genetic quality assurance (QA) testing and breeding strategies to minimize effects of random mutations and genetic drift.…”
Section: Immune Relevant Variations Among Substrainsmentioning
confidence: 99%